Hubungan Status Gizi Ibu Saat Hamil dengan Kejadian Stunting pada Balita Usia 0 - 24 Bulan di Puskesmas Sungai Raya Dalam - Sri Maryanti; Mia Dwi Agustiani; Dian Monalisa Rusliani (PPNI UNIMMAN, 2025)
Stunting in toddlers is a chronic nutritional problem caused by lack of nutritional intake due to feeding that does not meet basic needs. UNICEF data in 2024 shows that the infant mortality rate for toddlers is 48 per 1,000 live births and the neonatal mortality rate is 23 per 1,000 live births. Conditions that cause mortality and morbidity in infants and toddlers include malnutrition, sepsis, pneumonia, and premature birth (WHO, 2023). Factors that cause stunting include nutrition, health, environment, and socio-economy, such as malnutrition in pregnant women and children, recurrent infections, poor sanitation, and limited access to health services and nutritious food (Sari, 2023). The effects of stunting include brain development inhibitions, weakened immune systems, delayed psychosocial and motor development, and suboptimal physical growth. Based on a preliminary study at the Sungai Raya Dalam Health Center, there were 134 children under five who were stunted. This study aims to determine the relationship between maternal nutritional status during pregnancy and the incidence of stunting in toddlers aged 0–24 months. The research design used case control with a retrospective approach, involving 58 mothers with toddlers aged 0–24 months. The results showed that mothers with nutritional status with KELK had a higher risk of giving birth to stunted toddlers (72.7%) compared to mothers with good nutritional status (19.1%). The Fisher Exact test yielded a value of p = 0.000 (p < 0.05), which means that there is a significant relationship between the nutritional status of pregnant women and the incidence of stunting.